Strengthening Strategy of Human Capital in Community Program Management: A Case Study of Lali Gadget Village - Kusumawati, Ni Nyoman Andrani; Fedryansyah, Muhammad; Sulastri, Sri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Village Lali Gadget is a children's tourist destination located in Sidoarjo. This study aims to identify the strengths and weaknesses of human capital in the management of Kampung Lali Gadget and formulate implications for its development for the sustainability of the program. This study uses qualitative methods through in-depth interviews with initiators and managers, observation of activities, and documentation searches to support the analysis. Human capital analysis refers to the five components of human capital according to Mayo (2000), Individual Capability, Individual Motivation, Leadership, The Organizational Climate, and Workgroup Effectiveness. The results of the study show that Kampung Lali Gadget has strengths in commitment, adaptability, and strong collaboration. However, there are still limitations in technical capacity and uneven competency levels. These findings emphasize the importance of strengthening human capital to achieve the sustainability of Kampung Lali Gadget as a community-based educational and tourist space.